IMPLEMENTASI PENDEKATAN MANAJEMEN KASUS DALAM PENANGANAN TBC DI SENTRA REHABILITASI SOSIAL - Bambang Tri Hartono (LPPM Institut Pendidikan Nusantara Global, 2025)
Tuberculosis (TB) remains as a major public health challenge in Indonesia, particularly among vulnerable populations in social care institutions. Effective TB management requires not only medical intervention but also social services. This study explores the implementation of case management in TB handling at the Wirajaya Social Rehabilitation Center in Makassar, Indonesia, and identifies key strategic factors that influence service effectiveness. A qualitative descriptive approach was used, involving interviews, focus group discussions, observations, and document analysis. Thematic analysis and data triangulation ensured the validity of findings. Structured case management—featuring defined roles for case managers, supervisors, and case workers—enhanced coordination and service integration. Leadership, cross-sector collaboration, and self-care practices were critical in managing TB cases effectively and protecting staff. Case management is an effective and sustainable strategy for TB control in social institutions, promoting recovery while strengthening social service systems to address infectious disease challenges.